Iridium‐Catalyzed Dynamic Kinetic Stereoselective Allylic Etherification of Achmatowicz Rearrangement Products. Issue 3 (18th December 2017) - Zhu, Zhongpeng; Wang, Hao‐Yuan; Simmons, Christopher; Tseng, Po‐Sen; Qiu, Xiang; Zhang, Yu; Duan, Xiyan; Yang, Jing‐Kui; Tang, Weiping
Abstract: We recently developed a novel Ir‐catalyzed dynamic kinetic isomerization reaction for Achmatowicz rearrangement products. In this update, we show that products derived from the Achmatowicz rearrangement can also undergo Ir‐catalyzed dynamic kinetic allylic etherification in the presence of an appropriate ligand and additive to afford useful intermediates for the synthesis of carbohydrates. The addition of the triphenyl phosphite ligand shuts down the isomerization pathway and promotes the allylic etherification pathway. The addition of diphenyl phosphate improved the diastereoselectivity for the addition reaction. Interestingly, opposite diastereoselectivity was observed for sterically demanding alcohol nucleophiles compared to less sterically demanding alcohol nucleophiles. The method was also applied to the synthesis of several 2, 3‐dideoxypyranosides. Abstract :